2013
DOI: 10.1002/cncr.28331
|View full text |Cite
|
Sign up to set email alerts
|

Quantified pathologic response assessed as residual tumor burden is a predictor of recurrence‐free survival in patients with rectal cancer who undergo resection after neoadjuvant chemoradiotherapy

Abstract: Objective To determine whether quantified pathologic response assessed as a percentage of residual tumor cells predicts recurrence-free survival (RFS) in patients with rectal cancer. Methods We studied 251 patients with rectal adenocarcinoma treated with neoadjuvant chemoradiation and radical resection. Quantified pathologic response was defined as an estimated proportion of residual cancer cells in relation to the tumor bed: complete, no residual cancer cells; near complete, ≤5%; major, >5% and <50%; and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…Many studies have shown dramatic survival advantages by surgically minimizing the volume of cancers, including melanoma (1), brain (2), breast (3), and lung cancers (4). Otherwise, precancerous, cancerous, or normal tissue invaded by cancer cells remain (5)(6)(7). When these residual cells are not eradicated by adjuvant treatments, they give rise to recurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown dramatic survival advantages by surgically minimizing the volume of cancers, including melanoma (1), brain (2), breast (3), and lung cancers (4). Otherwise, precancerous, cancerous, or normal tissue invaded by cancer cells remain (5)(6)(7). When these residual cells are not eradicated by adjuvant treatments, they give rise to recurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al [28] studied 251 patients with locally advanced rectal adenocarcinoma who received preoperative CRT and found that recurrence-free survival did not differ between patients with pCR and those with nearly complete response (residual cancer cells ≤ 5%). Guillem et al [8] studied 297 patients with rectal cancer who received preoperative CRT and reported that the survival rate was significantly higher in patients with pCR or nearly pCR ( ≥ 95% tumor response) than in patients with other responses.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pCR [6,8,16,18,[26][27][28] and those with good tumor regression even in the absence of pCR [8,16,17,21,26,[28][29][30][31] have been reported to have good outcomes. Agarwal et al [28] studied 251 patients with locally advanced rectal adenocarcinoma who received preoperative CRT and found that recurrence-free survival did not differ between patients with pCR and those with nearly complete response (residual cancer cells ≤ 5%).…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of curative resection and sphincter-sparing surgery depending on the reduction in tumour size has been reported to increase with neoadjuvant chemoradiation (CRT) in patients with locally advanced rectal cancer (5). Preoperative radiotherapy (RT) is said to be more effective than postoperative RT (6).…”
Section: Abant Med J 2015;4(4):338-350mentioning
confidence: 99%